Análise do risco de ocorrência da monilíase em cacaueiro no Brasil face às mudanças climáticas globais - Moraes, Wanderson Bucker; de Jesus Junior, Waldir Cintra; Peixoto, Leonardo de Azevedo; Moraes, Willian Bucker [UNESP]; Furtado, Edson Luiz [UNESP]; da Silva, Lilianne Gomes; Cecílio, Roberto Avelino; Alves, Fábio Ramos (FapUNIFESP (SciELO), 2012)
The aim of this study was to evaluate the potential risk of moniliasis occurrence and the impacts of climate change on this disease in the coming decades, should this pathogen be introduced in Brazil. To this end, climate favorability maps were devised for the occurrence of moniliasis, both for the present and future time. The future scenarios (A2 and B2) focused on the decades of 2020, 2050 and 2080. These scenarios were obtained from six global climate models (GCMs) made available by the third assessment report of Intergovernmental Panel on Climate Change (IPCC). Currently, there are large areas with favorable climate conditions for moniliasis in Brazil, especially in regions at high risk of introduction of that pathogen. Considering the global warming scenarios provided by the IPCC, the potential risk of moniliasis occurrence in Brazil will be reduced. This decrease is predicted for both future scenarios, but will occur more sharply in scenario A2. However, there will still be areas with favorable climate conditions for the development of the disease, particularly in Brazil's main producing regions. Moreover, pathogen and host alike may undergo alterations due to climate change, which will affect the extent of their impacts on this pathosystem.
An analysis of the risk of cocoa moniliasis occurrence in Brazil as the result of climate change
Keywords: Geographic information system; Global warming; Moniliophthora roreri; Theobroma cacao; Crinipellis roreri